Effects of selective heart rate reduction with ivabradine on left ventricular remodelling and function: results from the SHIFT echocardiography substudy - Tardif, Jean-Claude (Oxford University Press, 2011)
AIMS: The SHIFT echocardiographic substudy evaluated the effects of ivabradine on left ventricular (LV) remodelling in heart failure (HF). METHODS AND RESULTS: Eligible patients had chronic HF and systolic dysfunction [LV ejection fraction (LVEF) ≤35%], were in sinus rhythm, and had resting heart rate ≥70 bpm. Patients were randomly allocated to ivabradine or placebo, superimposed on background therapy for HF. Complete echocardiographic data at baseline and 8 months were available for 411 patients (ivabradine 208, placebo 203). Treatment with ivabradine reduced LVESVI (primary substudy endpoint) vs. placebo [−7.0 ± 16.3 vs. −0.9 ± 17.1 mL/m(2); difference (SE), −5.8 (1.6), 95% CI −8.8 to −2.7, P< 0.001]. The reduction in LVESVI was independent of beta-blocker use, HF aetiology, and baseline LVEF. Ivabradine also improved LV end-diastolic volume index (−7.9 ± 18.9 vs. −1.8 ± 19.0 mL/m(2), P= 0.002) and LVEF (+2.4 ± 7.7 vs. −0.1 ± 8.0%, P< 0.001). The incidence of the SHIFT primary composite outcome (cardiovascular mortality or hospitalization for worsening HF) was higher in patients with LVESVI above the median (59 mL/m(2)) at baseline (HR 1.62, 95% CI 1.03–2.56, P= 0.04). Patients with the largest relative reductions in LVESVI had the lowest event rates. CONCLUSION: Ivabradine reverses cardiac remodelling in patients with HF and LV systolic dysfunction.